Long-term prognostic analysis of children and adolescents with differentiated thyroid carcinoma based on therapeutic response to initial radioiodine therapy - Wang, Congcong; Lu, Gaixia; Li, Yutian; Liu, Xinfeng; Wang, Guoqiang; Lu, Chenghui; Li, Jiao; Luo, Qiong; Zhang, Qian; Sun, Ming; Wang, Xufu; Wang, Renfei (Frontiers in Endocrinology, 2023)
Background: The clinical features and prognosis of children and adolescents with differentiated thyroid carcinoma (caDTC) are different from that of adults. Postoperative radioiodine therapy (RIT) was recommended for some intermediate and high risk caDTC patients. The objective of this study was to evaluate the long-term prognosis of pediatric caDTC patients with different responses to initial RIT and to explore the related influencing factors. Methods: All subjects were assigned to no clinical evidence of disease (NED) group, biochemical persistent disease (BPD) group, or structural/functional persistent disease (S/FPD) group based on the therapeutic response to initial RIT. Then, disease status was evaluated in all three groups at the last follow-up using ATA guidelines. Meanwhile, disease-free survival (DFS) for NED group and the progression-free survival (PFS) for the BPD and S/FPD groups were also assessed. Results: 117 subjects were divided into NED group (n=29), BPD group (n=48) and S/FPD group (n=34) after initial RIT. At the last follow-up, excellent response (ER), indeterminate response (IDR), biochemically incomplete response (BIR) and structurally incomplete response (SIR) rates were 93.10%, 6.90%, 0% and 0% in NED group; 29.17%, 25.00%, 43.75% and 2.08% in BPD group; and 11.77%, 2.94%, 0%, and 85.29% in S/FPD group. The 5-year DFS rate in NED group was 95.5%. The 5-year PFS rates in BPD and S/FPD groups were 79.2% and 48.6%, respectively. For children with structural or functional lesions, longer PFS were found in male children with 131I-avid lesions, and post-operative stimulated serum thyroglobulin (sti-Tg) < 149.80 ng/ml. Conclusions: The response to initial RIT could be helpful for defining subsequent treatment and follow-up strategies for caDTC patients. Post-operative sti-Tg and 131I-avidity of lesions are correlated with PFS.